2018
DOI: 10.1186/s12917-018-1623-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a streptomycin-resistant Mycobacterium bovis strain through antitubercular drug susceptibility testing of Tunisian Mycobacterium tuberculosis complex isolates from cattle

Abstract: BackgroundA rising isolation trend of drug-resistant M. bovis from human clinical cases is documented in the literature. Here we assessed Mycobacterium tuberculosis complex isolates from cattle for drug susceptibility by the gold standard agar proportion method and a simplified resazurin microtitre assay (d-REMA). A total of 38 M. tuberculosis complex strains, including M. bovis (n = 36) and M. caprae (n = 2) isolates, from cattle in Tunisia were tested against isoniazid, rifampin, streptomycin, ethambutol, ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Comparing this large number of the recorded mutations to the number of strains in the current study indicates the large‐scale polymorphisms in M. bovis genome (Djemal et al., 2018). Many efforts have been made for the development of computational methods to predict the effects of these mutations because experimental elucidating of their effects is expensive and time‐consuming.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Comparing this large number of the recorded mutations to the number of strains in the current study indicates the large‐scale polymorphisms in M. bovis genome (Djemal et al., 2018). Many efforts have been made for the development of computational methods to predict the effects of these mutations because experimental elucidating of their effects is expensive and time‐consuming.…”
Section: Discussionsupporting
confidence: 62%
“…Bovine tuberculosis (bTB) is a chronic contagious disease caused predominantly by M . bovis and infrequently by other pathogenic mycobacteria (Djemal et al., 2018; Romha et al., 2018). The disease has serious implications on animal health and severe socio‐economic impacts due to impaired milk and meat productivity, test and slaughter regime costs, culling of infected animals, carcass condemnation, movement controls and international trade restrictions (Vordermeier et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At present, mutation of the rst-line anti-tuberculosis drug resistance genes have been extensively studied at home and abroad, such as INH, RFP, EMB and SM. Studies showed that the mutation sites of the drug resistance genes of the above anti-tuberculosis drugs are quite different in different regions [21] .This study showed that the mutation rates of isoniazid resistance gene katG, rifampicin resistance gene rpoB, ethambutol resistance gene embB, streptomycin resistance gene rpsL and RRs in multidrug resistance group were higher than those in full-sensitivity group, which consistent with the results of domestic or foreign research [22][23][24][25] .However, there was no mutation in inhA gene of isoniazid-resistant group and full-sensitive group, which was inconsistent with the results of Asho Ali et al The results showed that the mutation rate of inhA gene was about 8% [26] . This difference may relate with geographical differences.…”
Section: Discussionsupporting
confidence: 86%
“…M. bovis exhibits an intrinsic resistance to pyrazinamide, a first-line anti-TB agent that is included in the standard treatment regimen offered to new TB patients [ 8 10 ]. Furthermore, reports of primary resistance to isoniazid, rifampicin and streptomycin primary resistance have recently emerged [ 3 , 8 ]. Multidrug resistant (MDR) forms of M. bovis have also been isolated [ 8 ].…”
Section: Introductionmentioning
confidence: 99%